2016
DOI: 10.1021/acs.est.5b03492
|View full text |Cite
|
Sign up to set email alerts
|

A Water-Withdrawal Input–Output Model of the Indian Economy

Abstract: Managing freshwater allocation for a highly populated and growing economy like India can benefit from knowledge about the effect of economic activities. This study transforms the 2003-2004 economic input-output (IO) table of India into a water withdrawal input-output model to quantify direct and indirect flows. This unique model is based on a comprehensive database compiled from diverse public sources, and estimates direct and indirect water withdrawal of all economic sectors. It distinguishes between green (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…India-specific consumptive water loss intensity factors and GHG emission factors for agriculture were sourced from Mekonnen and Hoekstra (2011) and Pathak et al (2010), respectively. A new data set developed by this team was used for assessing national-average crop water withdrawal and water intensity (blue and green) for food processing industries in India (Bogra et al 2016).…”
Section: Overview Of Methodsmentioning
confidence: 99%
“…India-specific consumptive water loss intensity factors and GHG emission factors for agriculture were sourced from Mekonnen and Hoekstra (2011) and Pathak et al (2010), respectively. A new data set developed by this team was used for assessing national-average crop water withdrawal and water intensity (blue and green) for food processing industries in India (Bogra et al 2016).…”
Section: Overview Of Methodsmentioning
confidence: 99%
“…Many economic–ecological assessments (Berrittella, Hoekstra, Rehdanz, Rosond, & Tol, 2007; Bogra et al., 2016; Lutter, Pfister, Giljum, Wieland, & Mutel, 2016; Ridoutt & Pfister, 2010; Velazquez, 2006; Mo, Zhang, Mihelcic, & Hokanson, 2011) indicate that water and other ecosystems goods and services ( EGS ) such as land, soil fertility, biodiversity, (Lenzen et al., 2012a; Tukker et al., 2016; Wood & Lenzen, 2003) make important contributions to socio‐economic systems. This implies that rising resource scarcities are capable of making socio‐economic‐ecological ( SEE ) systems vulnerable (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Rising regional water deficits (Dalin, Wada, Kastner, & Puma, 2017; WBCSD, 2016; Pfister, Koehler, & Hellweg, 2009; Rodell, Isabella Velicogna, & Famiglietti, 2009; Taylor et al., 2013) make India a water‐stressed country with growing population (UNDP, 2016) and affluence. Mapping flows of water in India's economic network for the year 2003–2004 has shown that both green (rainfall) and blue (ground and surface) (ISO14046, 2015; Mekonnen & Hoekstra, 2011) water make significant contributions to various sectors of the Indian economy (Bogra et al., 2016). Furthermore, the same study indicates that agriculture caused nearly 86% of withdrawals (excluding green water) throughout India, whereas Electricity required about 8% and domestic water supply 5% of blue water supply.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linear IO models applied to water typically combine input-output matrices and water accounts and apply a structural decomposition analysis that disaggregates the effects of a given shock on economic outputs and water use at different levels, from urban ) to multi-regional (Wan et al 2016). Because of their descriptive nature, researchers have frequently resorted to IO models to determine which sectors consume more water (directly and indirectly) (Bogra et al 2016), estimate their productivity (apparent and induced) (Duarte et al 2002), assess their exposure and vulnerability to shortages (Zhao et al 2015), and support the design of water and agricultural policy (González 2011;Llop 2008). Despite much progress, linear IO models still tackle two major issues insufficiently: (i) disruptions, such as droughts, are most often a disruption in the supply-side of the production chain; and (ii) modeling the substitution capabilities of other regions and/or other industries.…”
Section: Introductionmentioning
confidence: 99%